2018
DOI: 10.5897/ajar2018.13590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cutting length, time and growing media on the sprouting of dormant semi-hardwood cuttings of pomegranate cv. Wonderful

Abstract: Scientific confirmation of the traditionally known health benefits of pomegranates caused a tremendous increase in the consumption and production of this highly valuable fruit tree. Reproduction of pomegranate plants with seeds shows great variability in tree vigour and fruit quality. Cuttings is one of the most successful and preferred methods for the propagation of pomegranates. It is easy, quick, economic and most the convenient method of obtaining true-to-type trees in considerably less time; however, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…Again, the same interaction, as mentioned in many previous parameters, caused the significant value of shoot length of blackberry cuttings, (28) reported that the highest temperature obtained at the time of collection in September, favored the greater length of roots. These results are in parallel with those found by Higuchi et al, (15), Hussain et al, (16) in blackberry; Kahramanoğlu and Umar (17) in pomegranate, and Koyama et al, (20) in blueberry cutting propagation .…”
Section: Root Length (Cm)supporting
confidence: 90%
See 2 more Smart Citations
“…Again, the same interaction, as mentioned in many previous parameters, caused the significant value of shoot length of blackberry cuttings, (28) reported that the highest temperature obtained at the time of collection in September, favored the greater length of roots. These results are in parallel with those found by Higuchi et al, (15), Hussain et al, (16) in blackberry; Kahramanoğlu and Umar (17) in pomegranate, and Koyama et al, (20) in blueberry cutting propagation .…”
Section: Root Length (Cm)supporting
confidence: 90%
“…The result is in harmony with the findings of Higuchi et al, (15) and Hussain et al, (17). However, this result is in contrast with what was revealed by Koyama (20) who stated that the shorter cuttings led to a higher root dry mass.…”
Section: Root Dry Weight (G)supporting
confidence: 89%
See 1 more Smart Citation
“…February planting time resulted in maximum number of roots in present investigation. Ibrahim et al [17] used 500 and 1000 ppm of IBA and reported that the cutting taken in March from plant resulted in better rooting than those in late summer and early autumn.…”
Section: Resultsmentioning
confidence: 99%